Relaxion fluctuations (self-stopping relaxion) and overview of relaxion stopping mechanisms - Nayara Fonseca; Enrico Morgante; Ryosuke Sato; Géraldine Servant (Journal of High Energy Physics, 2020)
Abstract In implementations of the electroweak scale cosmological relaxation mechanism proposed so far, the effect of the quantum fluctuations of the homogeneous relaxion field has been ignored. We show that they can grow during the classical cosmological evolution of the relaxion field passing through its many potential barriers. The resulting production of relaxion particles can act as an efficient stopping mechanism for the relaxion. We revisit the original relaxion proposal and determine under which conditions inflation may no longer be needed as a source of friction. We review alternative stopping mechanisms and determine in detail the allowed parameter space for each of them (whether happening before, during and after inflation), also considering and severely constraining the case of friction from electroweak gauge boson production in models with large and Higgs-independent barriers.